2022
DOI: 10.3390/healthcare10091699
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Quality of Life in Patients with Non-Alcoholic Fatty Liver Disease May Be Associated with Depression and Fatigue

Abstract: Non-alcoholic fatty liver disease (NAFLD) is often thought of as clinically asymptomatic. However, many NAFLD patients complain of fatigue and low mood, which may affect their quality of life (QoL). This may create a barrier to weight loss and hinder the achievement of NAFLD therapy goals. Our study aimed to evaluate the QoL in NAFLD patients vs. healthy volunteers, and to analyze likely influencing factors. From March 2021 through December 2021, we enrolled 140 consecutive adult subjects (100 NAFLD patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
1
6
0
1
Order By: Relevance
“…Finally, according to the results of our study, the subgroup of NAFLD patients with sarcopenia reported substantially poorer QoL compared to the subgroup of NAFLD patients without sarcopenia, specifically, regarding the physical component of health, which complies with previously published data [ 39 ]. However, as far as we know the association of sarcopenia with reduced QoL among patients with NAFLD has not been previously reported.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, according to the results of our study, the subgroup of NAFLD patients with sarcopenia reported substantially poorer QoL compared to the subgroup of NAFLD patients without sarcopenia, specifically, regarding the physical component of health, which complies with previously published data [ 39 ]. However, as far as we know the association of sarcopenia with reduced QoL among patients with NAFLD has not been previously reported.…”
Section: Discussionsupporting
confidence: 90%
“…Even though NAFLD is an asymptomatic disease, the SMART-Liver program was also effective in managing NAFLD's nonspecific symptoms, such as fatigue. Recently, Golubeva et al [44] reported that fatigue was almost twice more common in patients with NAFLD than in those without it. However, chronic liver disease fatigue management remains a challenge because the pathophysiology of fatigue is complex.…”
Section: Principal Findingsmentioning
confidence: 99%
“…', 'had problems concentrating?'. A Likert scale response format was used for all items ranging from (1) meaning most impairment to (7) representing least impairment. Each domain was represented separately in the CLDQ-NAFLD score [19].…”
Section: Assessment Of Impaired Hrqlmentioning
confidence: 99%
“…Fatigue is associated with sleep deprivation, depression, and cardiovascular disease. Julia et al found that fatigue was nearly twice as common in patients with MAFLD [2,[5][6][7][8] . .…”
Section: Introductionmentioning
confidence: 99%